Towards Generative Governance: Co‐Creation With Emerging Technologies to Address Climate Challenges in Cities - Cesar Casiano Flores; A. Paula Rodriguez Müller; Evrim Tan (Urban Planning)
This thematic issue explores how co‐creation processes, facilitated by emerging technologies, can help cities in addressing complex climate adaptation challenges. Drawing on seven interdisciplinary contributions, this issue examines the roles of digital tools, participatory methods, and institutional innovations in fostering inclusive and collaborative governance. The contributions highlight diverse approaches, ranging from computational planning support systems and interactive lighting simulations to community‐based toolkits and scenario evaluators, that are implemented across various urban contexts. Collectively, they reveal both the opportunities for and the tensions of integrating emerging technologies into co‐creation processes. This editorial identifies four key enablers of co‐creation as generative governance—interactions, tools, processes, and institutions—and offers directions for future research at the intersection of digital innovation, collaborative governance, and climate adaptation. Together, the contributions provide a deeper understanding of how cities can design and support co‐creation initiatives that are inclusive, adaptive, and capable of building long‐term capacities to address climate change challenges.